Bigger Isn’t Always Better? Moderasi Ukuran Perusahaan pada Pengaruh Rasio Keuangan terhadap ROA di Industri Kesehatan yang terdaftar di BEI - Saragi, Nanda Putra (LPPM University 17 Agustus 1945 Samarinda, 2025)
This study investigates the influence of Debt to Equity Ratio (DER), Current Ratio (CR), and Total Asset Turnover (TATO) on Return on Assets (ROA), with Firm Size as a moderating variable in healthcare sector companies listed on the Indonesia Stock Exchange (IDX). A total of 28 companies were selected using purposive sampling, with data spanning from 2021 to 2024, resulting in 112 observations. Data analysis was performed using SPSS version 29. The findings show that DER has no significant effect on ROA. In contrast, both CR and TATO have a positive and significant effect on ROA. Furthermore, Firm Size does not moderate the relationship between DER, CR, and TATO on ROA. These results indicate that during the observed period, the profitability of health sector companies in Indonesia is primarily influenced by liquidity and asset turnover efficiency, rather than capital structure. Additionally, company size does not significantly strengthen or weaken the relationship between these financial ratios and ROA. Keywords: Debt to Equity Ratio, Current Ratio, Total Asset Turnover, Return on Assets, Firm Size, Moderation